Untying Pakistani Drama Dunya's Political Theory using Machiavellian Lens: A Critical Study - Sial, Imran Aslam; Zeeshan, Muhammad (Pakistan Languages and Humanities Review, 2025)
This study examines the popular Pakistani drama serial "DunyaPur" through the critical lens of Niccolò Machiavelli's political philosophy, specifically focusing on the characters' relentless "lust for power" and their willingness to employ "power at any cost." By analyzing key narrative arcs, character motivations, and strategic interactions, this research aims to identify and interpret the Machiavellian principles at play within the fictional world of "DunyaPur." The analysis explores that how the characters manipulate, deceive, and even disobey moral boundaries in their pursuit and maintenance of dominance, reflecting Machiavelli's observations on the acquisition and retention of political authority. In the end, this paper aims to investigate how "DunyaPur" presents the intricate interaction of ambition, strategy, and ethics in the framework of family and society power conflicts, so illuminating the continuing relevance of Machiavellian theory in comprehending human behavior inside a modern Pakistani narrative.